655.344.022.72.001.53 Analysis of compotions of the fountain solition for offset printing - Abduxalilova, Muxlisa; Babaxanova, Xalima (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract. Objective. The article analyzes the composition of the fountain solution, which is one of the significant components of the "ink – water" balance. Methods. An Express method was used to determine the chemical composition of the concentrate of the necessary concentrate and adjust the percentage of isopropyl alcohol to ensure the balance of "ink – fountain solution" and getting stable quality print. Results. The composition of the fountain solution received the results of the analysis on the gas chromatograph of the Agilent firm 8890 GC model. As a result, the gas chromatography method made it possible to quickly and accurately find out about the chemical composition of the fountain solution concentrate used in offset printing. Conclusion. According to the parameters of the resulting gas chromatography, the percentage of isopropyl alcohol that provides a “moisturizing solution-dye” balance is adjusted, depending directly on the type of moisturizing solution, drinking water properties, paint and printing material, and bellows the amount of concentrate, which makes it possible to obtain copies of consistent quality.